A fast and accurate global maximum power point tracking controller for photovoltaic systems under complex partial shadings - Adil Atoui; Mostefa Kermadi; Mohamed Seghir Boucherit; Khelifa Benmansour; Said Barkat; Fethi Akel; Saad Mekhilef (International Journal of Electrical and Computer Engineering (IJECE), 2023)
The operating conditions of partially shaded photovoltaic (PV) generators created a need to develop highly efficient global maximum power point tracking (GMPPT) methods to increase the PV system performance. This paper proposes a simple, efficient, and fast GMPPT based on fuzzy logic control to reach the point of global maximum power. The approach measures the PV generator current in the areas where it is almost constant to estimate the local maximums powers and extracts the highest among them. The performance of this method is evaluated firstly by simulation versus four well-known recent methods, namely the hybrid particle swarm optimization, modified cuckoo search, scrutinization fast algorithm, and shade-tolerant maximum power point tracking (MPPT) based on current-mode control. Then, experimental verification is conducted to verify the simulation findings. The results confirm that the proposed method exhibits high performance for complex partial irradiances and can be implemented in low-cost calculators.